Pengaruh Pemberian Ekstrak Kulit Pisang Kepok (Musa acuminata X Musa balbisiana ) terhadap Diferensial Leukosit pada Benih Ikan Kakap Putih (Lates calcarifer) - Hendriyono; Rika Wulandari; Aminatul Zahra (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2021)
The purpose of this study was to test the administration of Kepok banana peel extract with different concentrations against the differential of white snapper (Lates calcarifer) seed leucocytes. Maintenance was carried out for 23 days at HSRT Maju Mandiri Madong Village, Tanjungpinang City, Riau Islands Province. The production of banana peel extract takes place at the Marine Chemistry Laboratory of the Faculty of Marine and Fisheries Sciences, Raja Ali Haji Maritime University. This research was conducted experimentally by testing the extract of the banana peel of the white snapper. This study was designed using a completely randomized design (CRD) with 4 treatments (0 ppm, 0.5 ppm, 0.9 ppm, and 1.3 ppm) 3 replications. The results of this study showed that Kepok banana peel extract had a significant effect on the percentage of lymphocytes, neutrophils and hematocrit values ​​but had no significant effect on the growth and survival of white snapper fry. The use of Kepok banana peel extract mixed in the feed has a significant effect on the leucocyte differential, namely the percentage of lymphocytes and neutrophils in the white snapper fry. The best percentage of lymphocytes and neutrophils was in treatment C, with values ​​of 75.67% and 12.33% in white snapper fry.